OPTIMALISASI LAYANAN 5 LANGKAH POSYANDU DAN EDUKASI PENGGUNAAN OBAT BAGI KADER POSYANDU ILP - Lulu’ Luthfiya; Nadia Iha Fatihah; Anis Sovia Widyaningrum; Dian Triwulaningrum; Qothrunnadaa Rooiqoh; Meutia Annisa Hafiz; Naura Adila Muharrami; Dalva Sania Azzahra (PC IAI Sragen, 2026)
The transformation of Integrated Primary Care Posyandu (ILP) services emphasizes strengthening the role of community health cadres as frontline providers, particularly in optimizing the implementation of the five-step Posyandu service system and delivering accurate health information. In Ngrambe District, Ngawi Regency, limitations were identified in cadres’ understanding of the ILP five-step service flow and proper medication management according to the DAGUSIBU principles (Get, Use, Store, Dispose). This community service program aimed to enhance cadres’ knowledge and skills in optimizing ILP Posyandu services and promoting rational drug management. The program was conducted on February 24, 2026, at the Puskesmas Ngrambel, involving 49 ILP Posyandu cadres. Activities included preparatory assessment, educational sessions, anthropometric training, simulation of the five-step Posyandu service, and evaluation through pre-test and post-test. Data were analyzed using paired t-test with SPSS software. The results indicated a significant increase in cadres’ knowledge scores, from a mean of 9.37 to 9.71, with a significance value of 0.008 (p < 0.05). These findings demonstrate that the educational and mentoring approach effectively improved cadres’ understanding. Strengthening cadres’ capacity through participatory education is a strategic effort to enhance the quality of ILP Posyandu services and ensure responsible dissemination of medication-related information within the community.